Synthesis of the “PLAN DE SAUVEGARDE” using selected all-triploid oysters to reduce the shortage of spat in France due to OsHV-1–associated mortality in Crassostrea gigas - Dégremont, Lionel; Maurouard, Elise; Ledu, Christophe; Benabdelmouna, Abdellah (Aquaculture, 2019)
Due to massive mortality of Crassostrea gigas spat in France since 2008, a “plan de sauvegarde” was set up from 2011 to 2014 (hereafter referred to as PS1 to PS4), in order to reduce the shortage of spat. This plan involved the participation of commercial hatcheries, the French Research Institute for Exploitation of the Sea (Ifremer), and the Direction des Pêches Maritimes et de l'Aquaculture (DPMA) of the French Ministry of Agriculture. It was based on selecting diploid lines of C. gigas for their higher resistance to the oyster herpesvirus OsHV-1 (2nR group), and one of these lines was subsequently tetraploidized (4nR group). Both the 2nR and 4nR groups were produced by Ifremer, and then transferred to commercial hatcheries that produced the selected triploids (3nR groups). We report here the mortality rates of the 3nR group for each of the four “plan de sauvegarde” campaigns and compare these with the mortalities of the classic production of commercial hatcheries (both 2n and 3n), benchmarks of selected (2nR group) and unselected (2n-control group) oysters produced by Ifremer, and wild-caught spat, representing a total of 104 diploid and triploids batches. For PS1, the 3nR group had a mean mortality of 67% and did not show any advantage over the 2n- and 3n-commercial groups, suggesting a lack of genetic progress in the 2nR and 4nR groups. For PS2, OsHV-1 resistance was increased in both the 2nR and 4nR groups and, consequently, the 3nR group exhibited a mean mortality of 52%, which was significantly lower than the mortality of the 2n- (87%) and 3n-(76%) commercial groups in 2012. Unfortunately, the mortality of the 3nR group reached 62% and 71% in PS3 and PS4, respectively, although it was expected to be lower than that in PS2. OsHV-1 DNA was quantified in the live oysters at deployment (1356 oysters) and at the endpoint (1171 oysters), as well as in moribund oysters sampled during peak mortality (539 oysters). The results strongly supported the involvement of this pathogen during the main mortality outbreak ...